Kazbek – The First Czech Aroma “Flavor Hops” Variety: Characteristics and Utilization - Karel Krofta; Josef Patzak; Tomáš Sedlák; Alexandr Mikyška; Karel Štěrba; Marie Jurková (Kvasný průmysl, 2019)
The world market of craft beer, especially dry hopped beers, has been constantly growing in the last few years. That is why new varieties of hops are still being bred. This article gives the genetic, agronomic, chemotaxonomic and brewing characteristics of Kazbek, the first “flavor hops” variety bred in the Czech Republic. Kazbek genetically belongs to a group of bitter American hops resulting from Brewers Gold variety, but the alpha acids content is relatively low, 5.0–8.0% by weight. The content of a homologous series of geranyl esters (acetate – propionate – isobutyrate) in an amount 2–4% of total essential oils (1–1.5 g/100g) is considered to be the originator of the specific, mainly citrus-like aroma of Kazbek. Moreover, the essential oil fraction contains about 25 sulfurous substances, predominantly thioesters. In the pilot scale brewing tests, the quality of Kazbek hops was proved both in kettle and dry hopping of Pilsner lagers. The overall sensory impression of kettle hopped lagers was comparable to Saaz hops, the differences were in the character of hop-derived flavor and bitterness. The best results of dry hopped beers were achieved for a 2.5 g/l hop dose and a contact time of 3 days.